Pre-marriage Education: Fidelity in Buddhism - Tri Suyatno; Som Vechea (Jurnal Pendidikan, Sains Sosial, dan Agama, 2024)
Infidelity is a severe problem because it can destroy domestic life. In addition, the impact and causes of disloyalty are based on attention, adequacy in the economy, and the desire to try new things. Another factor that causes unfaithfulness is the lack of communication between the husband and the wife. This article aims to discover Buddhism's infidelity and how to overcome it. The method used in this study is qualitative. The essence of this study is that disloyalty can be classified as a violation of Buddhist pancasila. In addition, disloyalty leads to divorce and trauma for the child. The child will feel hatred for the parents and become the subject of anger from the parents. In addition, the impact and causes of disloyalty are based on attention, adequacy in the economy, and the desire to try new things. The attempt to handle this matter is the application of Sigalovada Sutta and Samvara to seek the continuity of the marriage. Applying each other's relationship is the main capital for the continuity of the marriage. Samvara, or self-control, and the correct implementation of precepts will positively impact domestic life